Collaborative actions to support SMEs’ sustainability in times of crisis - Zamfirache, Alexandra; Dragomir, Camelia-Cristina; Albu, Ruxandra-Gabriela; Foris, Tiberiu (Journal of Business Economics and Management, 2025)
The paper provides a detailed analysis of SMEs’ interest in collaborative action for sustainability as a way of responding to the challenges posed by recent crises. This study attempts to bridge the research gap on how managers of small and medium-sized enterprises manage business sustainability, providing complex insights into the application of collaborative practices for sustainability and the collaborative advantages that can support the competitiveness of these enterprises in the marketplace. The research design is quantitative and targeted 672 SMEs in Romania. A moderated moderation analysis is also carried out, and the model tests the relationship between the age of the analysed SMEs and the impact felt after recent crises, a relationship moderated by sustainable cooperation, and a moderator moderated by possible changes felt from the application of collaborative practices. Finally, this regression function is statistically significant and was shown to be a significant moderated moderation. The research results showed the major impact of recent crises on the activity of SMEs, indicating that the interest of these companies in collaborative actions and the level of results expected from collaboration for sustainability decreases the greater the impact of crises on their business.